2013
DOI: 10.5334/ijic.1501
|View full text |Cite
|
Sign up to set email alerts
|

Managing mental illness in primary care - General Practitioners' perspective

Abstract: Background: The Agency for Integrated Care (AIC) conducted a survey to determine the specific areas in which the agency could work with General Practitioners (GPs) to enhance mental illness management in Singapore. This survey was conducted as part of AIC's engagement strategy and because the Primary Care Surveys 2010 and 2005 noted that a sizeable number of mental health cases are seen by GPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…We were unable to determine if the sociodemographic profile of the GPs was representative of overall GPs in Singapore, although it was similar to that reported in previous studies conducted among GPs. 50,51 The response rate was just over 50%, thus, responses might not be strongly representative given the low response rate, and the resulting non-response bias may limit the generalisability of the results. However, our response rate of 52% in this mailing study involving GPs was higher than that reported in other similar studies 17,18 and the results are an important first step towards engaging GPs in dementia care.…”
Section: Factor 4: Trainingmentioning
confidence: 99%
“…We were unable to determine if the sociodemographic profile of the GPs was representative of overall GPs in Singapore, although it was similar to that reported in previous studies conducted among GPs. 50,51 The response rate was just over 50%, thus, responses might not be strongly representative given the low response rate, and the resulting non-response bias may limit the generalisability of the results. However, our response rate of 52% in this mailing study involving GPs was higher than that reported in other similar studies 17,18 and the results are an important first step towards engaging GPs in dementia care.…”
Section: Factor 4: Trainingmentioning
confidence: 99%
“…These findings were comparable with the results of previous surveys of GPs in Singapore. 22 23) The proportion of patients with ID constituted 1% to 5% of the overall patient population for most GPs who responded to the survey. This indicates that patients with ID constitute only a minor part of their work, which might make GPs less confident or inexperienced in dealing with these patients over time.…”
Section: Discussionmentioning
confidence: 99%
“…Among the GPs who were seeing patients with mental illness, depression (23%) was one of the most common mental illnesses attended to. [6] These findings were admittedly conservative estimates of the local prevalence of depression since studies have indicated that in Asian societies, somatic symptoms of depression may be more salient to patients and could be mistakenly reported merely as symptoms of organic ailments. [7] Studies have shown that treatment adherence and positive treatment outcomes could be predicted by patients' perception of their illness, the severity of their illness, and their expectation that the illness will improve with treatment.…”
mentioning
confidence: 99%